Development of sex- and genotype-specific behavioral phenotypes in a Shank3 mouse model for neurodevelopmental disorders - Bauer, Helen Friedericke; Delling, Jan Philipp; Bockmann, Jürgen; Boeckers, Tobias M.; Schön, Michael (Frontiers in Behavioral Neuroscience, 2023)
Individuals with Shank3 related autism spectrum disorders (ASDs, Phelan McDermid Syndrome) exhibit a profound global developmental delay, language impairment and muscular hypotonia. Also common are repetitive behaviors and altered social interactions. In this comprehensive study we focused on the developmental aspect of ASD related behaviors in a Shank3 mouse model (exon 11 deletion) and examined the animals at an early time point, corresponding to adolescence, and a late time point, starting at 13 weeks of age in the categories of social behavior, cognition, communication, and motor skills. Interestingly, the animals showed relatively similar phenotypes at the two different time points of analysis and severe impairments in motor coordination and endurance in the grid hanging test was detected, while muscle strength (grip strength) was unchanged. Surprisingly, the animals showed only minor differences in social and communication behavior, but pronounced stereotypic and repetitive behaviors. Some behavioral tests indicate increased anxiety and slightly impaired cognitive flexibility, while spatial learning and memory were rather normal. Female animals had similar abnormalities as males, but often with lower penetrance in most of the tests. In most behavioral tests heterozygous Shank3 KO animals showed only slight differences compared to WT mice. Accurate characterizations of mouse models for genetic diseases and/or syndromes is a necessity to understand the pathophysiology of genetically defined disorders. It is the basis for finding suitable readouts for compound screenings and reduces animal testing in preclinical trials.